Quintais agroflorestais e estado nutricional familiar na comunidade Santa Maria, Santarém - PA - GUIMARÃES, Ariane Souza (Universidade Federal do Oeste do Pará, 2021)
In this work we studied the presence of agroforestry gardens and the nutritional status of the families in the community of Santa Maria-situated in the region of Strong Axis, on the left bank of the highway Fernando Guilhon. All elements, climate, soil, fauna and flora, are so closely related, cannot consider any of them as the primary. All contribute to the maintenance of the balance of the ecosystem. As natural resources include all elements of fauna, flora, water and soil, in consumption direct use of these resources. For subsistence consumption occurs by crops designed in known space and called backyards. It was verified that the main function of the backyards to these families is not the economic function, but food needs. Showed that the presence of the backyards is of extreme importance, so much so that most farmers try to pass on the knowledge to their children in order to . In relation to nutritional assessment carried out, 7 adults meet the nutritional diagnosis of eutrophy (healthy), 2 have the nutritional diagnosis of overweight and obesity 1. 8 of the children evaluated are with the nutritional diagnosis of eutrophy, overweight 1 and 2 presented low weight. It is extremely important to perform both age groups nutritional follow-up and encourage the cultivation and maintenance of backyards, because the same guarantee the complementation of feeding families, in addition to being sources of vitamins and fiber, ensuring the reference to the concept of food security, namely, the right of all to adequate food.